Socio-Demographic and Clinical Profile of Admitted Patients for Psychiatric Illness in a Tertiary Care Military Hospital in Bangladesh (IAHS Medical Journal, 2024)
Background: Mental health problems are becoming a public health issue in all countries around the world. It’s often ignored and unnoticed by patients, their relatives and society as well. Treatments for all these disorders are as available as efficacious. The purpose of this study was to assess the socio-demographic and clinical profile of admitted patients for psychiatric illness in a tertiary care military hospital.Materials and methods: This hospital based retrospective study was performed by analyzing the medical records of admitted psychiatric patients, carried out in the Department of Psychiatry at Combined Military Hospital (CMH), Chattogram from 01 July 2022 to 31 December 2022. For this purpose, 41admitted patients in psychiatry ward of CMH Chattogram were enrolled in the study. Psychiatric diagnoses of the patients were assigned by the consultant psychiatrist as per International Classification of Diseases (ICD) 10th Revision diagnostic criteria. Statistical analyses were carried out by using the Statistical Package for Social Sciences (SPSS)-version 16. The quantitative observations were indicated by frequencies and percentages. Ethical issues were maintained all through the study.Results: The results showed that more than half of (56.09%) patients were in 19-35 years of age with male preponderance (63.41%) and most of the cases reported from urban area (58.53%). The most common psychiatric morbidity among the patients were major depressive disorder (26.82%) followed by Anxiety disorder (17.07%) and Obsessive- compulsive disorders (17.07%). In this study majority of patients stayed 15-28 days (80.48%) on an average of 21.5 days.Conclusion: Neurotic cases were predominant in psychiatric admission. Results of this study may help in the planning for better mental health service integrated with primary healthcare system of our country. Findings of this study will also act as an eye-opener for psychiatrists regarding a wide range of psychiatric diagnoses as well future research in psychiatric fraternity.IAHS Medical Journal Vol 6(2), December 2023; 19-23